Virtually Sacred: Sacred Space, Ritual, and Narrative in Assassin's Creed, Far Cry, and The Talos Principle. - Atkinson, Andrew (Journal of Religion & Popular Culture)
This article explores the use of sacred space in contemporary video games, arguing that there are two dominant moments of unconsciously secular engagement with sacred space that are quite common in gaming, and are present, in particular, in the Assassin's Creed and Far Cry series--one attracting the gamer to the space, the second transgressing the rituals of reverence associated with the space. There is a third, less dominant, perhaps emerging trend in gameplay that recreates sacred space and attitudes according to the semiotics and/or spatial reconfiguration internal to the game. I critique this approach in Monument Valley, Fez, and The Talos Principle.